Phimosis - physiology vs pathology? - Michał Raban; Artur Żak; Jakub Litak; Rafał Smoliński; Agnieszka Budny; Monika Turska (Kazimierz Wielki University, 2017)
Introduction: Phimosis is one of many conditions which causes concern among parents of young boys. It appears when the foreskin of the penis cannot be pulled back past the glans. The main reason is the foreskin opening tightness or narrowing. This defect can be congenital or acquired. The condition is diagnosed on the basis of a physical examination performed by a physician.Aim of the study: The aim of the study is to present the disease unit with a special focus on proper medical diagnosis and treatment.Summary: It should be noticed that in most cases phimosis is a physiological state. Surgery is not recommended at this time. Then parents or caregivers should be advised about the nature of the child's condition to avoid possible complications and to provide appropriate care for the patient.